2002
DOI: 10.1046/j.1540-8167.2002.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Troponin I Levels After Spontaneous Implantable Cardioverter Defibrillator Shocks

Abstract: Serum cTnI rises occur in the majority of patients after multiple (>3) spontaneous ICD discharges but are due to acute coronary syndrome only 14% of the time (22% of the time in patients with known coronary artery disease).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 4 publications
1
46
0
Order By: Relevance
“…The positive and negative predictive values of an elevated troponin level were 21% and 94%, making troponin testing a valuable tool in excluding significant myocardial injury after trauma. Other reasons for traumatic troponin elevation include implantable cardioverter defibrillator shocks (28) and infiltrative disorders such as amyloidosis (29). It has been postulated that extracellular amyloid deposition may lead to myocyte compression injury, leading to myocardial damage and troponin release.…”
Section: Direct Myocardial Damagementioning
confidence: 99%
“…The positive and negative predictive values of an elevated troponin level were 21% and 94%, making troponin testing a valuable tool in excluding significant myocardial injury after trauma. Other reasons for traumatic troponin elevation include implantable cardioverter defibrillator shocks (28) and infiltrative disorders such as amyloidosis (29). It has been postulated that extracellular amyloid deposition may lead to myocyte compression injury, leading to myocardial damage and troponin release.…”
Section: Direct Myocardial Damagementioning
confidence: 99%
“…9) The cause of increased risk may be postulated that the negative inotropic consequences of the shock itself could increase the risk of death, especially when the patient receives multiple shocks due to oversensing or in response to ongoing supraventricular tachycardia. [10][11][12][13] Thus, effective strategies to reduce ICD shocks are desirable. Antiarrhythmic medication is frequently administered in patients with an ICD.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in animal experiments and human studies, it has been shown that the voltage gradients in the heart are lower during S-ICD defibrillation as compared to transvenous ICD defibrillation; S-ICD defibrillation is also not associated with troponin release. (13)(14)(15)(16) Nevertheless, the S-ICD system is not without its disadvantages. When compared to transvenous ICD systems, S-ICD systems can only provide backup pacing following a shock, as pacing from the subcutaneous position invariably causes painful muscle stimulation.…”
Section: A 4bmentioning
confidence: 99%
“…Therefore, S-ICD systems cannot provide antitachycardia pacing to painlessly terminate VT. In addition, as the energy needed by the S-ICD system to defibrillate is approximately three-fold higher than that needed by transvenous ICD systems, (13,14) the pulse generator of the S-ICD system is more bulky than the current generation of transvenous ICD systems. (17,18) It measures 78 mm × 65 mm × 15 mm, with a volume of 69 cc and a mass of 145 g, which is almost twice the size of a traditional ICD.…”
Section: A 4bmentioning
confidence: 99%